STUDY OF THE PROCESS OF CRUSHING STEM WEIGHT - Saichuk, O. V.; Avetisyan, V. K.; Kolpachenko, N. M.; Manilo, V. L.; Bilovod, O. I.; Dudnyk, V. V. (Scientific Progress & Innovations, 2021)
The article substantiates and reveals the solution of the problem of preserving the sharpness of the cutting edges of knives during the grinding of the stem mass of cereals. It was found that taking into account the ratio obtained in the work, it is possible to perform numerical calculations of the effect of compression layer thickness on the thickness of the cutting edge of the knife, if you set a certain value h and known properties of the material to be cut (τ, σ). An expression is obtained that allows to analyze the dependence of the blade sharpness, taking into account the design features of real knives (radius of curvature). These calculations depend on the height of the compression layer (for h=const) and the height of the source layer (for hst=const), or on both parameters of the height of the layer with a known relationship between them. The study found that the formula derived by V. P. Goryachkin, for reasons of minimum energy consumption for cutting, although it does not take into account the geometry of the cutting edge, still allows you to determine the optimal angle of sharpening knife, if you set its thickness and width of the cutting edge. Graphs for calculations of the optimal thickness of the cutting edge under the condition of n-fold compression of the layer at the time of cutting are proposed. The dependences for calculating the influence of the thickness of the crushed stem mass on the thickness of the cutting edge of the knife, as well as a reasonable angle of sharpening of the knife, which provides a minimum cutting force. The proposed calculations and recommendations on the selected research topic should be used when using existing structures and designing new elements of combine harvesters for crushing the stem mass of cereals. The results of the study should be implemented in the educational process in the preparation of graduates of specialties 208 Agricultural Engineering and 133 Industrial Engineering.